Physical, psychological, and behavioral problems among children and adolescents in countries with different economic statuses during the COVID-19 pandemic: a systematic review and meta-analysis - Peng, Bo; Reeves, Kara K. L.; Lee, Shara W. Y.; Chung, Tina H. Y.; Hui, Heidi W. L.; Leung, Alfred H. L.; Pang, Johnson C. Y. (Frontiers in Pediatrics, 2023)
The COVID-19 pandemic has impacted children and adolescents’ physical activity (PA), sleeping patterns, and psychological and behavioural health. Yet, little is known about the differences on those in countries with various economic status. Articles published from database inception through March 16, 2022 were retrieved using the CINAHL Complete, Cochrane Library, EMBASE, Medline, PubMed, and PsycINFO. High quality studies that reported the number of participants with parameters associated with PA, sleeping patterns, psychological and behavioural problems in young people age under 18 years during the pandemic were included. We referenced the Canadian 24-Hour Movement Guidelines for PA and sleep duration to provide the event rate for young people who were not compliance to the guidelines. The event rate of young people who had decreased sleep quality and experienced psychological and behavioural problems were also investigated. Subgroup analysis was conducted to identify the differences in those in countries with diverse economic status. Funnel-plot analysis and Egger’s test was also conducted to identify any risk of publication bias. A total of 66 studies with 1,371,168 participants age between 0 to 18 years, involving 27 countries were included. During the pandemic, we identified 41% (95%CI: 39%, 43%; I2=96.62) and 43% (95%CI: 34%, 52%; I2=99.42) of young people did not meet the PA and sleep duration recommendation guidelines. In addition, 31% (95%CI: 28%, 35%; I2=99.66) of young people had decreased their sleep quality. Yet, no significant difference was found across countries with difference economic status. However, the event rates of participants with psychological and behavioural problems were 32% (95%CI: 28%, 36%; I2=99.85) and 19% (95%CI: 14%, 25%; I2=99.72) respectively. And the rate of psychological problems was more severe in those who live in lower-middle income countries (p<0.001), while the rate of behavioural problems was more severe in those who live in high incomes countries (p=0.001). During the pandemic, the discouragement of PA, poor sleep quality and high risk of psychological and behavioural problems are concerning. Large number of young people did not comply with the recommendation guidelines. Timely implementation of recovery plans is critical to address the adverse effects on young people.